Cross‐cultural representations of conjoined twins. Issue 2 (13th May 2021) - Tekendo‐Ngongang, Cedrik; Williams, Keith J.; Williams, Marc S.
Abstract: Conjoined twinning is a rare birth defect estimated to occur in about 1 in 50, 000 to 100, 000 births. The mechanism of conjoined twinning is not proven. Different forms of conjoined twinning are observed with the thoracopagus form being the most common. The rate of conjoined twinning is similar across all major populations. A dramatic malformation of this type would be an extraordinary occurrence leading people to reflect on the spiritual or supernatural nature of such an event. Therefore, it is not surprising that artifacts that seem to depict different forms of conjoined twins are seen across diverse cultures. In this article, we present a survey of these cultural artifacts including anatomic classification based on external anatomy and an exploration of the cultural and spiritual contexts associated with the artifacts. A key finding is that the most common form of conjoined twinning in the artifacts is parapagus (both dicephalus and diprosopus) in contrast to thoracopagus, the most common form in epidemiologic studies. Potential reasons for this difference are discussed. Evidence is presented to support the speculation that these objects represent artistic impressions of actual conjoined twinning events.